Crystal structure of betulinic acid methanol monosolvate - Wei Tang; Neng-Hua Chen; Guo-Qiang Li; Guo-Cai Wang; Yao-Lan Li (Acta Crystallographica Section E, 2014)
The title compound [systematic name: 3β-hydroxylup-20(29)-en-28-oic acid methanol monosolvate], C30H48O3·CH3OH, is a solvent pseudopolymorph of a naturally occurring plant-derived lupane-type pentacyclic triterpenoid, which was isolated from the traditional Chinese medicinal plant Syzygium jambos (L.) Alston. The dihedral angle between the planes of the carboxylic acid group and the olefinic group is 12.17 (18)°. The A/B, B/C, C/D and D/E ring junctions are all trans-fused. In the crystal, O—H...O hydrogen bonds involving the hydroxy and carboxylic acid groups and the methanol solvent molecule give rise to a two-dimensional network structure lying parallel to (001).